Исследование влияния параметров полиаксиального винта на напряженно-деформированное состояние сегментов позвоночника с системой фиксации - Пионтковский, В. К.; Веретельник, Юрий Викторович (НТУ "ХПИ", 2007)
У статті запропоновано параметричну модель біомеханічної системи "сегмент суглоба – система кріплення з поліаксіальним гвинтом". Отримано залежності характеристик напружено-деформованого стану від конструктивних параметрів гвинтів та параметрів їх установки відносно тіла хребця.

The parametrical model of biomechanical system "segment of joint – the fastening system with polyaxial screw" is offered in the article. Dependences of characteristics of stressedly-deformed state from the structural parameters of screws and parameters of their setting in relation to the body of vertebra are obtained.
Keywords: эндопротезирование; костно-металлический блок; биохимическая система; метод конечных элементов; травматичность; костная ткань